Potential of bean flour in the development of gluten-free bread with added nutritional value (Research, Society and Development, 2020)
Despite the expressive growth in the research and the market for gluten-free products, gluten-free breads (GFB) still have unsatisfactory appearance, texture, and taste, in addition to low nutritional content and short-shelf life. Thus, the improvement of the technological and nutritional properties of GFB is still a challenge. The incorporation of alternative raw materials rich in nutrients and bioactive compounds, such as legumes, is a strategy to improve the nutritional quality and diversify these products. Bean flour (BF) has potential as a food ingredient and its use may contribute to the development of new products, strengthening the production chain and it can promote health and nutrition of consumers. Based on this, the objective of this study was to evaluate the potential of BF in the gluten-free breadmaking. A 2² factorial design with three center points was used to investigate the effects of level variations of BF (0 to 100% flour base – fb) and water (W) (150 to 200% fb) in the physical properties, proximate composition and acceptability of GFB. It was used response surface methodology and main component analysis to define the optimum formulation. Results indicate the potential of BF in the gluten-free breadmaking, showing that the incorporation of 50% BF was able to improve the loaf specific volume, reduce the crumb firmness and hardness, in addition to increasing the levels of ash, protein and dietary fiber, reaching GFB with high fiber content.